Monetary Policy Transmission in Ghana : Does the Interest Rate Channel Work? - Kovanen, Arto (IMF Working Papers; Working Paper ;, 2011)
This paper analyzes interest rate pass-through in Ghana. Time series and bank-specific data are utilized to highlight linkages between policy, wholesale market, and retail market interest rates. Our analysis shows that responses to changes in the policy interest rate are gradual in the wholesale market. Prolonged deviation in the interbank interest rate from the prime rate illustrate the challenges the Bank of Ghana faces when targeting a short-term money market interest rate. Asymmetries in the wholesale market adjustment possibly relate to monetary policy signaling, weak policy credibility, and liquidity management. In the retail market, pass-through to deposit and lending interest rates is protracted and incomplete.1.